Quicksilver - Stephenson, Neal (Stephenson, Neal. Baroque cycle, 2006)
The exploits of an alchemy-rejecting scientist, a vagabond leader, and a former Turkish harem prisoner intersect in the world of the American colonies, the Tower of London, and the courts of France, in a novel set against the backdrop of the late seventeeth century and early eighteenth century. By the author of Cryptonomicon.